Lucky CEOs and Lucky Directors - BEBCHUK, LUCIAN A.; GRINSTEIN, YANIV; PEYER, URS (Journal of Finance, 2010)
ABSTRACT We study the relation between opportunistic timing of option grants and corporate governance failures, focusing on “lucky” grants awarded at the lowest price of the grant month. Option grant practices were designed to provide lucky grants not only to executives but also to independent directors. Lucky grants to both CEOs and directors were the product of deliberate choices, not of firms’ routines, and were timed to make them more profitable. Lucky grants are associated with higher CEO compensation from other sources, no majority of independent directors, no outside blockholder on the compensation committee, and a long‐serving CEO.